Introduction of an RS1 mutation causative variant consistent with identified XLRS patient using CRISPR/Cas9 technology in normal iPSC - Sun, Xihao; Mao, Shengru; Liang, Yuqin; Duan, Chunwen; Cui, Zekai; Gu, Jianing; Jiang, Bing; Ding, Chengcheng; Chen, Jiansu; Tang, Shibo (Stem cell research, 2024)
X-linked retinoschisis (XLRS) is a common retinal genetic disease that occurs in juvenile males and causes progressive visual impairment. This presents a schisis in the macula or peripheral retina of bilateral eyes, which has no effective treatment. Here, we introduced the RS1 (c.C304T, p.R102W) mutation into a normal induced pluripotent stem (iPS) cell line using CRISPR/Cas9 technology. This missense mutation was consistent with that observed in the XLRS patient-derived iPS cell line (CSUASOi001-A). Conclusively, establishing a directed gene mutation cell line (CSUi007-A) provides a useful cell resource to investigate XLRS pathogenesis.